2016
DOI: 10.1016/j.freeradbiomed.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mitochondrial redox state using NADH and NADPH autofluorescence

Abstract: The redox states of the NAD and NADP pyridine nucleotide pools play critical roles in defining the activity of energy producing pathways, in driving oxidative stress and in maintaining antioxidant defences. Broadly speaking, NAD is primarily engaged in regulating energy-producing catabolic processes, whilst NADP may be involved in both antioxidant defence and free radical generation. Defects in the balance of these pathways are associated with numerous diseases, from diabetes and neurodegenerative disease to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
297
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(311 citation statements)
references
References 188 publications
(294 reference statements)
13
297
0
1
Order By: Relevance
“…Though previous studies have demonstrated that the majority of cellular NAD + (>75%) is located inside the mitochondria (Tischler et al 1977;Di Lisa and Ziegler 2001), the cytosolic NAD + /NADH redox potential is reported to greatly exceed the mitochondrial NAD + / NADH potential (Williamson et al 1967;Jones and Sies 2015;see Sahlin et al 2002 for discussion), suggesting that lactate oxidation is favoured outside of the mitochondrial matrix. In the cytosol, this is due to the equilibrium constant for the associated redox couples (namely, lactate/pyruvate) combined with influential protein binding sites for NADH (Jones and Sies 2015); changes in NADH are therefore primarily mitochondrial (Sun et al 2012;Blacker and Duchen 2016). Indeed, consistent with the present study, lactate oxidation only occurs when NAD + is added.…”
Section: Discussionsupporting
confidence: 80%
“…Though previous studies have demonstrated that the majority of cellular NAD + (>75%) is located inside the mitochondria (Tischler et al 1977;Di Lisa and Ziegler 2001), the cytosolic NAD + /NADH redox potential is reported to greatly exceed the mitochondrial NAD + / NADH potential (Williamson et al 1967;Jones and Sies 2015;see Sahlin et al 2002 for discussion), suggesting that lactate oxidation is favoured outside of the mitochondrial matrix. In the cytosol, this is due to the equilibrium constant for the associated redox couples (namely, lactate/pyruvate) combined with influential protein binding sites for NADH (Jones and Sies 2015); changes in NADH are therefore primarily mitochondrial (Sun et al 2012;Blacker and Duchen 2016). Indeed, consistent with the present study, lactate oxidation only occurs when NAD + is added.…”
Section: Discussionsupporting
confidence: 80%
“…The effect of pH on NADH based FLIM has been performed before to understand the stress response and involvement of NADPH production in related to the ROS(reactive oxygen species) production(57,58). Although there has been report of FLIM-NADPH response with ROS(59), currently there are no accurate ways to robustly characterize this response. The intensity drop between time 2.4 hours and 6.6 hours shows possible photobleaching over time or couple of apoptotic cells which reduced the number of cells in the image over time.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently one has to be aware of the fact that the measured autofluorescence is always a mixture of both NADPH and NADH (33). Consequently one has to be aware of the fact that the measured autofluorescence is always a mixture of both NADPH and NADH (33).…”
Section: Nadph (Detection Related)mentioning
confidence: 99%